The effects and comparison between listening to Al-Quran and control group on archery performance / Muhammad Taufiq Mohd Shahari - Mohd Shahari, Muhammad Taufiq (Faculty of Sport Science and Recreation, 2016)
Al-Quran is the central religious book for Muslims which it is believed that it have the power beyond the content. The purpose of this study was to analyse the effect of listening to Al-Quran in archery performance and to investigate the differences between listening to AI-Quran and Music. A total of 57 subjects were chose in these study and were divided into two groups which were experimental group and control group, 29 for experimental group and 28 for control group. Before the experimental procedure starts, the participants were explained about the aim of the study. They were given 6 bows of arrows to shoot for pre score. Then they will listen to the AI Quran for experimental group and music for control group. They will listen to AI Quran and music for 15 minutes of Surah Yaseen and music of PacheIbel's Canon D major. After that, the subjects will go for post shooting score with 6 bows of arrows immediately after listening to the Al-Quran and music. The results shows the archers that listen to AI-Quran have higher mean score with 46.3448 points compare to music with 36.5357. It is possible that the archers listening to AI-Quran contribute in better accuracy performance compare to listening to music